Research Topics in Medicines and How Our Board Members Are Engaged in Them - Sakagami, Hiroshi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
With the development of analytical instruments, the academic system has become more complicated, producing new journals one after another. Therefore, it became much important to clarify what is original of "Medicines". As the name Medicines indicates, it includes science and practice of caring for a patient and managing the diagnosis, prognosis, prevention, treatment or palliation of their injury or disease. Therefore, Medicines differs from other journals with similar title in that it covers a wide range of fields, from traditional medicine to rapidly developing molecular-targeted drugs, focusing on their pharmacological effects, structure-activity relationships, metabolic pathways, gene expression, using cultured cells, animals, and clinical trials. Most parts of this Special Issue were written by our editorial board members, who described the research topics and how they are engaged in their field of research. All of these articles are their life-long story. We collected a total number of 22 original works by basic researchers and clinical doctors. We hope that readers can get a chance to know the current status of diverse fields of medicines, and what your most important research themes are after reading these articles.